Sustained coral reef growth in the critical wave dissipation zone of a Maldivian atoll - Kench, Paul S. (2023)
Sea-level rise is expected to outpace the capacity of coral reefs to grow and maintain their wave protection function, exacerbating coastal flooding and erosion of adjacent shorelines and threatening coastal communities. Here we present a new method that yields highly-resolved direct measurements of contemporary reef accretion on a Maldivian atoll reef rim, the critical zone that induces wave breaking. Results incorporate the suite of physical and ecological processes that contribute to reef accumulation and show growth rates vary from 6.6 ± 12.5 mm.y−1 on the reef crest, and up to 3.1 ± 10.2 mm.y−1, and −0.5 ± 1.8 mm.yr−1 on the outer and central reef flat respectively. If these short-term results are maintained over decades, the reef crest could keep pace with current sea-level rise. Findings highlight the need to resolve contemporary reef accretion at the critical wave dissipation zone to improve predictions of future reef growth, and re-evaluate exposure of adjacent shorelines to coastal hazards.